Psychological/behavioral interventions for emerging adults with chronic pain - Foy, Judith G.; Kechichian, Sandra; Foy, Michael R.; Ziadni, Maisa (Frontiers in Pain Research, 2024)
Background Emerging adults, of whom significant numbers report chronic pain, are characterized as having unique needs and challenges. Psychological/behavioral treatments found to be beneficial for reducing pain outcomes in children and adults are understudied in emerging adults. Following a systematic review of the literature, our objective is to report on quantitative studies of psychological/behavioral interventions for chronic pain in emerging adults. Method We conducted a search of six databases (Cochrane Central Register of Controlled Trials, Google Scholar, ProQuest, PsycINFO, PubMed, and Web of Science) and reference sections in dissertations and systematic reviews to 4/29/2023. Keywords and phrases were search term combinations of “chronic/persistent pain”, “emerging/young adults,” and “intervention/treatment” using Boolean logic. Results Our review resulted in identifying 37 articles, of which 2 duplicates were removed, and 31 were further excluded by a screening process based on various inclusionary and exclusionary criteria. The search yielded four studies on psychological/behavioral interventions (yoga, acceptance and commitment therapy and relaxation), all of which positively affected the pain experience and/or pain-related outcomes. These studies presented issues in design such as not being blinded or randomized, having a small sample size, and potential confounds that were not reported or examined. Discussion The low number of studies reveals a large gap in the literature and is a call-to-action to further expand our understanding of effective and safer psychological/behavioral therapies for chronic pain in emerging adults. Successful pain management during this developmental phase may help young adults achieve positive trajectories for personal, occupational, relational, and health aspects of their lives.